Investigation on the self-assembly of the NFL-TBS.40-63 peptide and its interaction with gold nanoparticles as a delivery agent for glioblastoma - H. Alnemeh-Al Ali; A. Griveau; F. Artzner; A. Dupont; N. Lautram; M.A. Jourdain; J. Eyer (Elsevier, 2022)
NFL-TBS.40-63 peptide is a recently discovered peptide derived from the light neurofilament chain (NFL). In this study, we demonstrated that the Biotinylated-NFL-peptide (BIOT-NFL) can spontaneously self-assemble into well-organized nanofibers (approximately 5 nm width and several micrometers in length) in several solutions, whereas the typical self-assembly was not systematically observed from other peptides with or without coupling. The critical aggregation concentration that allows the BIOT-NFL-peptide to aggregate and auto associate was determined at 10−4 mol/L by surface tension measurements. X-ray scattering of BIOT-NFL-peptide also demonstrated its beta-sheet structure that can facilitate the intermolecular interactions involved in the self-assembly process. The possible disassembly of self-assembled BIOT-NFL-peptide-nanofibers was examined via a dialysis membrane study. We further investigated the interaction between nanofibers formed by BIOT-NFL-peptide and gold nanoparticles. Interestingly, a strong interaction was demonstrated between these nanoparticles and BIOT-NFL-peptide resulted in the formation of BIOT-NFL-peptide-nanofibers grandly decorated by gold nanoparticles. Finally, we investigated the internalization of gold nanoparticles coupled with BIOT-NFL-nanofibers into F98 rat glioblastoma cells, which was increased compared to the non-coupled control gold nanoparticles. All these results indicate that this peptide could be a promising therapeutic agent for targeted delivery.